(untitled) (Analysis in Theory and Applications, 2020)
We present a direct and short proof of the non-degeneracy of the harmonic structures on the level-n Sierpinski gaskets for any n≥ 2, which was conjectured by Hino in [1,2] and confirmed to be true by Tsougkas [8] very recently using Tutte's spring theorem.